2010
DOI: 10.1007/s00421-010-1560-1
|View full text |Cite
|
Sign up to set email alerts
|

Exhaustive exercise reduces TNF-α and IFN-α production in response to R-848 via toll-like receptor 7 in mice

Abstract: Stressful exercise results in temporary immune depression. However, the impact of exercise on the immune responses via toll-like receptor (TLR) 7, which recognizes the common viral genomic feature, single-stranded RNA, remains unclear. To clarify the effect of stressful exercise on immune function in response to viral infection, we measured the changes in the plasma concentration of tumor necrosis factor (TNF)-α and interferon (IFN)-α, which are induced downstream from the TLR-ligand interaction, in exhaustive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0
2

Year Published

2011
2011
2019
2019

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 40 publications
0
25
0
2
Order By: Relevance
“…Further, intense aerobic treadmill exercise increases pro-TNF-alpha and anti-IL-10 and pro-apoptotic protein (caspase 3), indicating an overall anti-inflammatory effect as a result of wheel running in healthy mice [46]. Likewise, exhaustive exercise reduces TNF-alpha and IFN-alpha concentrations and this reduction is via TLR-7 and elevation of systemic catecholamines [47]. Further, hepatic inflammation and fibrosis is reduced by reduction of TNF-alpha, macrophage infiltration and tissue inhibitor of matrix metalloproteinase-1 mRNA [48].…”
Section: B Exercise and Anti-inflammatory Effectsmentioning
confidence: 99%
“…Further, intense aerobic treadmill exercise increases pro-TNF-alpha and anti-IL-10 and pro-apoptotic protein (caspase 3), indicating an overall anti-inflammatory effect as a result of wheel running in healthy mice [46]. Likewise, exhaustive exercise reduces TNF-alpha and IFN-alpha concentrations and this reduction is via TLR-7 and elevation of systemic catecholamines [47]. Further, hepatic inflammation and fibrosis is reduced by reduction of TNF-alpha, macrophage infiltration and tissue inhibitor of matrix metalloproteinase-1 mRNA [48].…”
Section: B Exercise and Anti-inflammatory Effectsmentioning
confidence: 99%
“…This is, to our knowledge, the first study to demonstrate that IFN-b production in response to poly I:C is maintained, even though the mice are subjected to exhaustive exercise stress. A previous study showed that exhaustive exercise inhibited INF-a production in mice when the mice were treated by R-848 as activator of TLR7 [7]. A difference function between poly I:C/TLR3 and R-848/TLR7 might have occurred via a [11,12] despite viral ssRNA binding to TLR7 [10].…”
Section: Resultsmentioning
confidence: 97%
“…One group contained exhaustive exercising mice (EX, n = 12), and the other group contained non-exercising mice (N-EX, n = 11). The EX mice were run on a treadmill to exhaustion, and N-EX mice were kept at rest [4,7]. Mean time to exhaustion for EX mice was 65 ± 2 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Strenuous exercise-induced TNF-α suppression in plasma is observed following stimulation with PGN/TLR2, poly I:C/TLR3 75) , R-848/TLR7/8 76) and CpG DNA/TLR9 (Fig. 6).…”
Section: Strenuous Exercise-induced Tnf-α Suppression In Response To mentioning
confidence: 99%